A study of clinico-demographic profile of patients with dissociative disorder - Shah, SK (Journal of College of Medical Sciences-Nepal, 2013)
Objectives To study the clinical and socio demographic profile of patients with dissociative disorder and their comorbid mental illness. Materials and methods Fifty-one patients of dissociative disorder presenting to emergency and outpatient department of Psychiatry at College of Medical Sciences Teaching Hospital during the period from Jan to March 2012 were included. International statistical classification of diseases and related health problems tenth edition, diagnostic criteria for research (ICD-10, DCR) was used. Results Out of 51 patients, the majority 24 (47.1%), were in the age group 15-29. However the age of presentation ranged from 9-45 years. The females were more, 44 (86.3%) as compared to males 7 (13.7%). The majority of patients had low level of education with none of the patients having education above intermediate level. The majority of patients, 27(52.9%) belonged to lower middle class. 49% of the patients presented with dissociative convulsions, 15.7% with dissociative motor disorders, 15.7% with dissociative stupor, 11.8% with dissociative anesthesia and sensory loss and 7.8% with trance and possession disorder. Depressive illness was found co-morbid with dissociative disorder in 33.3%, borderline personality disorder in 9.8% and histrionic personality disorder in 7.8%. There was history of immediate stressful events that supposedly precipitated the event in 76.5%. Conclusion Dissociative disorder mainly affects young female of lower socio-economic and educational status with history of immediate stressful life events precipitating the illness. Journal of College of Medical Sciences-Nepal, 2012, Vol-8, No-3, 30-35 DOI: http://dx.doi.org/10.3126/jcmsn.v8i3.8683